A cointegration tests on Malaysian Government Securities (MGS) spreads and inflation / Cheng Fan Fah and Annuar Nasir - Fah, Cheng Fan; Nasir, Annuar (2012)
The purpose of this research is to study the relationship between yield spreads of Malaysian Government Securities (MGS) and inflation dynamics over the period of 1976 to 2008. The study used various statistical techniques to determine the predictive power of yield spreads between 1-year MGS and 10-years MGS in inflation movement. The quarterly data provide evidences that the cointegration test explains that there is a long-run cointegration relationship between the MGS spreads and GDP deflator. The result is further supported by the Granger causality test where there is a unidirectional relationship running from GDP deflator to spreads. The evidence found here is consistent with the theory that inflation is Granger-caused by spreads. The result from regression indicates that linear relationship exists between MGS quarterly yield spreads and inflation. The efficiency of regression model is confirmed by Durbin-Watson test and residual plots.